Analisis Pola Sidik Jari Tangan dan Jumlah Sulur Serta Besar Sudut ATD Penderita Diabetes Mellitus di Rumah Sakit Umum Daerah Jambi - Siburian, Jodion; ANGGREINI, Evita; Hayati, S.F. (Universitas Jambi, 2010)
The number of Diabetes Mellitus(DM) patient in Indonesia tends to increase over the years that put the country in the forth largest number of DM patient in the world. DM becomes one of the main death-causing diseases in Indonesia. Dermatoglyph is a technique that can be employed tohelp diagnose diseases caused by genetic disorder, including early detection for DM. The research aims to reveal the comparison between the DM patients and non DM Patients in terms of finger printpattern, finger ridge number, and ATD angle. The research was undertaken in the Jambi Provincial public hospital by observing 50 DM patients. The collected data were analyzed using Chi Square and t-student tests. The results show that DM patients and non-patients perform difference finger print pattern frequency (X 2:10,8). DM patient tend to have higher arch pattern that that of non-patients.However, the finger ridge number and ATD angle do not indicate any different between DM patients and non-patients.